The complex landscape of contemporary fathering in the UK. (18th May 2016) - Meah, Angela; Jackson, Peter
Abstract: Distinguishing between fatherhood as a social construction and fathering as a social practice, this paper presents empirical evidence from the UK concerning the complex landscape of contemporary fathering. The paper focuses on the spatial and temporal dynamics of fathering, particularly following moments of rupture and transition such as family break-up or bereavement. Based on narrative interviews and ethnographic observation, including the co-production and analysis of video data, the paper identifies three key issues: the diversity of contemporary fathering practices, the complex emotional geographies of lone fathering and the relationality of fathering both in terms of the research participants and their female partners (as fathers and mothers) and inter-generationally (between the research participants and their own fathers). The study supports previous research on the 'awkward spaces' of fathering with a particular emphasis on moments of transition and their complex social and emotional geographies.